Full Orthotropic Mechanical Characterization of Pinus radiata Plywood Through Tensile, Compression and Shear Testing with Miniaturized Specimens - Saavedra-Flores, E (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
This study introduces and validates a miniaturized testing methodology for the complete orthotropic characterization of structural plywood, including out-of-plane directions that are typically difficult to access. Novel small-scale geometries were developed for tension and shear configurations, with compliance corrections applied to ensure accurate stress–strain responses. The method proved reliable and sensitive to mechanical differences arising from veneer architecture, adhesive type, and interfacial bonding. Two sets of 18 mm structural plywood panels—manufactured with distinct adhesive systems, one bio-based (F1) and one phenol-formaldehyde (F2)—were systematically tested under tensile, compressive, and shear loading in ten orthogonal configurations (Tx, Ty, Tz, Cx, Cy, Cz, τxy, τyx, τxz, τyz), following standards NCh 3617, EN 789, and ASTM B831. Tensile moduli were approximately twice the corresponding compressive values, while out-of-plane moduli reached only 6–11% of in-plane values. F1 exhibited higher stiffness in both tension and compression, particularly in transverse directions, due to thicker perpendicular veneers enhancing bending restraint and shear coupling. In contrast, F2 achieved greater peak shear strength owing to its more uniform veneer structure, which improved stress distribution and delayed interlaminar failure. Observed asymmetry between tension and compression reflected microstructural mechanisms such as fiber alignment and cell-wall buckling. The miniature-specimen data provide reliable input for constitutive calibration and finite-element modeling, while revealing clear links between veneer-thickness distribution, shear-transfer efficiency, and macroscopic performance. The proposed framework enables efficient, reproducible orthotropic characterization for optimized, lightweight, and carbon-efficient timber systems. © 2025 by the authors.